Hybridization K-Pop Aesthetics and Western Pop Culture in BTS' Music Video 'Butter' Through Circuit of Culture - ‘Ouelya, Dyiena Hanieviya; Muniroch, Sri (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2025)
This research examines how BTS’s music video Butter represents cultural hybridization between Korean and Western pop cultures through Stuart Hall’s Circuit of Culture theory. Although hybridization in K-Pop has been widely discussed, in depth analysis of visual aesthetics in music videos stays limited. This research addresses the gap by analyzing Butter through five interconnected aspects, regulation, production, representation, consumption, and identity, which collectively construct complex and transnational cultural meanings. The research employs a qualitative method using thematic and semiotic analysis of choreography, costumes, set designs, and other visual symbols. Data validity is strengthened through triangulation by analyzing the official Butter music video, audience comments on YouTube, TikTok, and Instagram, as well as producer interviews published in Variety. The results show that Butter blends cultural elements such as retro Western fashion with Korean-style choreography, the use of English lyrics to reach an international audience, and the building of BTS’s identity through emotional engagement with fans. This hybridization shows a cultural negotiation process rather than merely a market strategy. The research confirms that BTS successfully integrates Korean cultural elements into a global framework, creating cross-cultural appeal that reinforces their position as international cultural icons.